2020
DOI: 10.1080/19420862.2020.1752529
|View full text |Cite
|
Sign up to set email alerts
|

Multimeric antibodies with increased valency surpassing functional affinity and potency thresholds using novel formats

Abstract: The success of therapeutic antibodies is largely attributed for their exquisite specificity, homogeneity, and functionality. There is, however, a need to engineer antibodies to extend and enhance their potency. One parameter is functional affinity augmentation, since antibodies matured in vivo have a natural affinity threshold. Generation of multivalent antibodies is one option capable of surpassing this affinity threshold through increased avidity. In this study, we present a novel platform consisting of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…In addition, the engineered dimeric ACE2-Fc has been shown to interfere with virus infection 9 . Our work on self-assembling antibodies showed that increasing valency enhances the functional a nity 11 and we have applied this method to increasing the valency of ACE2. We have carefully established the molecular characteristics of the Quad protein ACE2-Fc-TD protein showing that the tetravalency of the ACE2 domains is displayed to facilitate potency increase and is the most e cacious of the proteins tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the engineered dimeric ACE2-Fc has been shown to interfere with virus infection 9 . Our work on self-assembling antibodies showed that increasing valency enhances the functional a nity 11 and we have applied this method to increasing the valency of ACE2. We have carefully established the molecular characteristics of the Quad protein ACE2-Fc-TD protein showing that the tetravalency of the ACE2 domains is displayed to facilitate potency increase and is the most e cacious of the proteins tested.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since soluble ACE2 has a short in vivo residence 10 , the creation of high molecular weight tetramers should facilitate long circulation times. Moreover, the tetramerization technology 11 is full exible and easily adapted to any new proteins that may be devised. The method involves simple protein engineering and allows production of secreted multimeric proteins with high yields.…”
Section: Discussionmentioning
confidence: 99%
“…To increase binding avidity, and to enhance agonism through receptor clustering, there has been considerable interest in high valency 5 antibody formats that present more than two antigen-binding sites (2,3). Current techniques for creating multivalent antibody-presenting formats include chaining together multiple antigen-binding fragments (4,5), pentameric immunoglobulin M (IgM) or IgM derivatives such as fragment crystallizable (Fc) domain hexamers (6), inorganic materials fused to multiple dimeric immunoglobulin G (IgG) antibodies (7), or protein oligomers or nanoparticles to which immunoglobulin (Ig) or Ig-binding domains are linked (8)(9)(10)(11)(12)(13). While these approaches are effective at multimerizing antibodies, they often require extensive engineering or multiple-step conjugation reactions for each new desired antibody oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach goes beyond previous computational design efforts to create functional nanomaterials by integrating form and function; whereas previous work has fused functional domains onto assemblies constructed from separate structural components(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)27), our AbCs employ antibodies as both structural and functional components. By fashioning designed antibody-binding, cage-forming oligomers through rigid helical fusion, a wide range of geometries and orientations can be achieved.…”
mentioning
confidence: 99%
“…This leads to higher functional affinity through valency and avidity effects 1, 35 . The implementation of our protein engineering method using the human p53 protein tetramerization domain is a simple and flexible method to increase valency 1,30 . Since community transmission is a major problem with SARS-CoV-2 and the appearance of new variants that appear to have increased transmissibility 23,24,26,27 there is a need for effective rapid, sensitive testing.…”
Section: Super-charging Antibodies With Enhanced Neutralization Potenmentioning
confidence: 99%